Crystallization and lamellar nanosheet formation of an aromatic dipeptoid. Issue 42 (3rd May 2019) - Castelletto, Valeria; Chippindale, Ann M.; Hamley, Ian W.; Barnett, Sarah; Hasan, Abshar; Lau, King Hang Aaron
Abstract : An aromatic peptoid analogue of the diphenylalanine dipeptide self-assembles in aqueous solution and the first crystal structure was obtained for this class of compound. Abstract : An aromatic peptoid analogue of the diphenylalanine dipeptide self-assembles in aqueous solution and the first crystal structure was obtained for this class of compound. This reveals molecular packing stabilized by networks of hydrogen bonds. Free-floating nanosheet lamellar structures are observed in solution, which form via cooperative intermolecular interactions driven by π stacking.